(untitled) (Rehabilitation and Recreation, 2024)
The article discusses data from recent scientific research dedicated to the analysis and comparison of anthropometric indicators in 11-year-old children with visual impairments compared to their relatively healthy peers. Due to partial or profound impairment of the visual analyzer and its functions, the authors suggest that these children exhibit significant lag in physical development. Scientists note low anthropometric indicators, specifically in body weight, height, chest circumference, and chest excursion in children with visual impairments. The goal of the research is to conduct a comparative analysis of anthropometric indicators in 11-year-old children with visual impairments and their relatively healthy peers. Research Methods. The study involved 20 children: 11-year-old, comprising 10 children with visual impairments attending the Educational and Rehabilitation Center “Zoresvit” in Odesa, and 10 relatively healthy children. The healthy children received basic secondary education at the Supportive Educational Institution “Vypasnyansky Educational Establishment of General Secondary Education” of the Molohivska village council in the Bilhorod-Dnistrovskyi district of the Odesa region. The scientific research was conducted in accordance with the fundamental principles of the “Ethical Principles for Conducting Human Research” as outlined in the Helsinki Declaration (1964–2013). The accomplishment of the research objectives was carried out using commonly accepted methods: including theoretical analysis of scientific literature on the chosen research topic, standard anthropometry, and mathematical data processing. Results. In conducting a comparative analysis of these indicators in groups of 11-year-old children with visual impairments and their relatively healthy peers, it is noted that for some of these indicators, children with visual dysfunctions exceed their peers. These indicators include body weight and body length by both absolute and sigma values, as well as the chest excursion indicator. However, corresponding statistical analysis showed that the difference between the groups is statistically significant only for body weight indicators (p<0.01), while for the rest of the indicators, the differences do not reach statistical significance. In other words, 11-year-old children with visual impairments significantly differed from their relatively healthy peers primarily in terms of body weight, both in kilograms and in sigma assessments, taking into account age-specific norms. Conclusions. The difference in anthropometric indicators between groups of children with visual impairments and their relatively healthy peers is statistically significant only for body weight indicators (p<0.01). This suggests that children with visual impairments have significant differences in body weight compared to their healthy peers. Interestingly, for the rest of the investigated indicators, differences do not reach statistical significance. This may indicate that, despite visual impairments, other aspects of physical development in these children may be similar to their healthy counterparts. The conducted comparative analysis of anthropometric indicators highlights that some children with visual dysfunctions exceed their peers, specifically in terms of body weight and body length indicators by both absolute and sigma values.